The Influence of Using Genre Based Approach on Students Procedural Writing Text Skill (A True Experimental Study at the Ninth Grade in SMPN 11 Kota Serang) - Tresna, Nia; Rahmawati, Eri; Evenddy, Sutrisno Sadjie (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2020)
This research was aimed to determine whether there was an influence of using genre based approach on students procedural writing text skill. The method used a quantitative method with true-experimental study. The population was ninth grade students of SMPN 11 Kota Serang with 66 students were taken as sample. There were two groups, experimental and control group. Each of which consisted of 33 students. Different treatments were given to the experimental group while the control group taught by conventional teaching. The test of writing instrument was administered in two sections; pretest and posttest. The data were counted with content validity, reliability, normality test,homogeneity test,and hypothesis test (t-test). The result of this research was that using genre based approach has positive influences such as the students could enjoy the process of learning and facilitated the student needs in mastering students’ writing skill. The result of the data in this research showed that the score of the average of post-test was bigger than pre-test and the result of analyzing in independent t-test showed that with level significance 0.05 % was 8.289 ≥ 1.997. It means that there was an influence of using genre based approach on students’ writing text skill at ninth grade in SMPN 11 Kota Serang.